Study of Serum Homocysteine Level in Young Patients with Myocardial Infarction and Cerebrovascular Stroke - Daveshwar, Meena Rajiv; Shah, Hiral Samir; Zaveri, Ankit (Annals of Pathology and Laboratory Medicine, 2019)
Background: Nowadays, vascular disease is the leading cause of death and disability. India too is facing epidemic of cardiovascular and cerebrovascular disease. The established risk factors for heart disease and stroke account for one half to three fourth of cases. The remainders are the result of other factors that promote atherosclerosis. Elevated blood levels of homocysteine have been linked to increased risk of premature coronary artery disease, stroke and thromboembolism, even among people who have normal cholesterol levels. Hence screen for homocysteine is recommended in patients with premature atherosclerotic disease and unexplained venous thrombosis. Methods: The present study was performed to correlate the levels of serum homocysteine levels in young patients (</=40 yrs) with myocardial infarction and ischemic cerebrovascular stroke. Thirty cases were studied along with assessment of their risk factor. Result: It was observed that serum homocysteine levels were significantly raised in coronary artery disease and ischemic stroke patients. Conclusion: Increase levels of homocysteine is an important factor that assesses risk independently for coronary artery disease and ishchemic stroke.